Roadmap to COP28 - (:unkn) unknown (My University, 2023)
This report examines Africa’s evolving role in global climate governance, assessing its strategic positioning ahead of COP28. It traces the continent’s shift from fragmented national negotiations to a unified stance under the African Union, highlighting key milestones in African climate diplomacy. The study analyzes the main outcomes of COP27, focusing on climate finance, adaptation, loss and damage, and just transition strategies. It also explores Africa’s climate vulnerabilities, policy challenges, and the need for structural reforms in financial institutions to address the continent’s climate finance gap. As COP28 approaches, the report provides a roadmap for Africa’s engagement, emphasizing enhanced financial commitments, sustainable development pathways, and a just transition framework that aligns climate resilience with economic growth. It contributes to the discourse on Africa’s agency in climate negotiations, reinforcing its role as a proactive actor in shaping global climate policy.
Keywords: African Research